2018
DOI: 10.20319/pijss.2018.41.591610
|View full text |Cite
|
Sign up to set email alerts
|

From Microfinance to ‘‘Gintingan’’: Reinventing Local Institutions for Poverty Reduction in Indonesia

Abstract: Poverty has been acknowledged as a fundamental problem in development. It is so pervaded so the United Nations's has put 'no poverty' as the first objective to be achieved in the Sustainable Development Goals (SDGs). As a 15 th biggest countries in the world in terms of Gross Domestic Product, Indonesia are has been struggling in combating poverty with the increased proportion of inequality and most of its inhabitants are economically vulnerable. Although Microfinance has been believed as a tool to reduce pove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Research that describes the strategy of higher education in building entrepreneurial bureaucracy is still rarely conducted. There are several studies on this issue, such as conducted by Qurtubi [25], Saefullah [26], and Sakapurnama [27], which studied reinventing higher education in Indonesia. These studies do not specifically explain the strategy of higher education in building an entrepreneurial bureaucracy.…”
Section: Introductionmentioning
confidence: 99%
“…Research that describes the strategy of higher education in building entrepreneurial bureaucracy is still rarely conducted. There are several studies on this issue, such as conducted by Qurtubi [25], Saefullah [26], and Sakapurnama [27], which studied reinventing higher education in Indonesia. These studies do not specifically explain the strategy of higher education in building an entrepreneurial bureaucracy.…”
Section: Introductionmentioning
confidence: 99%
“…Several research has found relationship between microfinancial institution and reduced poverty (Choudhury et al, 2017;Mazumder & Wencong, 2013). Microfinance can serve as an instrument for empowerment to achieve increased public income and reduced poverty (Saefullah, 2018). Robinson (2001) argues that poverty alleviation can be carried out by means of various programs, one of which is microfinancial service.…”
Section: Introductionmentioning
confidence: 99%